ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANI JAGUNG (Zea mays L) DIDESA SIMPANG AGUNG KECAMATAN SIMPANG KABUPATEN OKU SELATAN - rosita meizi; ema pusvita; septianita septianita (JASEP, 2022)
This study aims to determine the factors that affect the income of corn farming in Simpang Agung village, Simpang district, South OKU district. The method used in this research is a survey method. The sampling method used in this study is a simple random sampling method (sample random sampling). Data analysis used income formula, SPSS multiple linear regression and risk analysis formula. The results of this study are: The average income received by corn farming in Simpang Agung Village, Simpang District, OKU Selatan Regency is Rp. 32,422,600 ha/year where the average income is Rp. 46,398,666 ha/year and the average total cost of production is Rp. 13,876.733 ha/yr. The results of this study show partially (t-test) for the education variable (X1) with a t-count value less than t-table, experience (X2) with a t-count value less than t-table, variable amount of production (X3) with a t-count value more from t table, variable number of workers (X4) with t count value less than t table, variable land area (X5) with t count less than t table. So it can be concluded that education, experience, total production, number of workers, and land area have a significant effect on the factors that affect maize farming income in Simpang Agung Village, Simpang District, South OKU Regency. Corn farming in Simpang Agung Village, Simpang District, South OKU Regency produced a coefficient of variation of CV 1.82 more than 0.5 and an L value of more than 0 32,522,483 and the conclusion was that the farming was protected from losses.Keywords: Factor, income, corn, risk